Presence of the red imported fire ant at gopher tortoise nests - Michelina C. Dziadzio; Andrea K. Long; Lora L. Smith; Richard B. Chandler; Steven B. Castleberry (Wildlife Society Bulletin)
ABSTRACT Red imported fire ants (Solenopsis invicta; fire ants) are predators of turtle (Testudine) eggs and hatchlings, but little information is available indicating how and when fire ants detect turtle nests during incubation. Therefore, during 2014, we compared fire ant presence at gopher tortoise (Gopherus polyphemus) nests in burrow aprons in early and late incubation with paired burrow aprons that did not contain eggs. To determine whether fire ants were attracted to soil disturbance associated with nesting, we compared fire ant presence at physically disturbed burrow aprons without eggs (i.e., simulated empty nests) with paired burrow aprons with no disturbance or eggs at Ichauway, Georgia, USA. We found fire ants more frequently at nests than at paired aprons early in incubation, but not late in incubation. Additionally, we found no difference in fire ant presence between simulated empty nests and paired sites. Our results indicate that fire ants are attracted to gopher tortoise nests because of a factor other than the initial soil disturbance that accompanies nest deposition, possibly the mucous and moisture released by the female as eggs are laid. © 2016 The Wildlife Society.